Pemanfaatan Teknologi Digital Dalam Meningkatkan Kesejahteraan Masyarakat Pesisir - Rohman, M. Izanur; Darmaningrum, Khaerunnisa Tri (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2024)
The advantages of digital technology have been seen in recent years. The purpose of this study is to determine the advantages and added value of this digital technology. The rapid adoption of digital technology in coastal areas will be discussed in this study. The discussion focuses on several issues, including the following: (1) the use of digital technology; (2) the impact felt from its use. Identifying the types of technology used and articles with empirical data. The identification results show the range of technology used, including artificial intelligence applications, users of digital technology in education and health, and the types of activities that utilize it.